FIELD EVALUATION OF POPULAR BT COTTON HYBRIDS AGAINST BLIGHT DISEASE UNDER NATURAL EPIPHYTIC CONDITION ALTERNARIA (Journal of Plant Disease Sciences, 2023)
A significant crop that brings in a respectable living for millions of farmers in both developed and developing nations is cotton. In addition to increased yield, farmers are beginning to favour Bt cotton due to its ability to effectively control the bollworm complex. Thirty pathogens are known to attack Bt cotton in India. Among these are rusts, grey mildew, blight, and bacterial blight, which all result in Alternaria significant yield losses in cotton of 20 to 30 percent. These diseases are also economically significant. In the current study, 51 commercially available Bt cotton hybrids were evaluated for the disease in 2022–2023 at the Main Agricultural Research Station in Raichur, under epiphytic natural settings. Of the 51 hybrids that were assessed against the blight, eight genotypes (ARCH 3132 BG II, SS 246 Alternaria BG II, C 7940 BG II, C 7939 BG II, KCH 9122 BG II, ACH 151-2 BG II, CT 018 BG II, and DC 5130 BG II) were resistant to tested disease, while 28 genotypes were only moderately resistant. Further, 12 genotypes were moderately susceptible and 3 genotypes were susceptible to thedisease.
Keywords: Alternaria blight; Bt cotton,; Host resistance; Screening